Cavity-aided quantum parameter estimation in a bosonic double-well Josephson junction - Semião, F. L. (2015)
We describe an apparatus designed to make nondemolition measurements on a Bose-Einstein condensate trapped in a double-well optical cavity. This apparatus contains, as well as the bosonic gas and the trap, an optical cavity. We show how the interaction between the light and the atoms, under appropriate conditions, can allow for a weakly disturbing yet highly precise measurement of the population imbalance between the two wells and its variance. We show that the setting is well suited for the implementation of quantum-limited estimation strategies for the inference of the key parameters defining the evolution of the atomic system and based on measurements performed on the cavity field. This would enable de facto Hamiltonian diagnosis via a highly controllable quantum probe.